Boosting MSME Performance and Competitive Advantage Through Strategy and Innovation: Insights From Malang City - Aisyah, Nabila Nur; Arif, Moh. Erfan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of business strategy and innovation on competitive advantage among MSMEs in Malang City, with business performance as a mediating variable. Design/Methodology/Approach – This study employs a quantitative research approach using Partial Least Squares (PLS) analysis. Data were analyzed using SmartPLS to evaluate the outer and inner models and to conduct hypothesis testing. The analysis examines the direct and indirect relationships among business strategy, innovation, performance, and competitive advantage. Findings – The results indicate that business strategy has a significant positive effect on competitive advantage, while innovation does not have a significant direct effect on competitive advantage. Furthermore, business strategy significantly influences business performance, and innovation also has a significant effect on performance. Business performance significantly affects competitive advantage and mediates the relationship between business strategy and competitive advantage with a positive indirect effect. However, innovation has a significant negative indirect effect on competitive advantage through performance. These findings highlight the important role of business performance in translating strategic initiatives into competitive advantages for MSMEs. Originality/Value This research is original in simultaneously examining business strategy, innovation, and performance within a mediation framework to explain competitive advantage among MSMEs. The findings provide practical value by guiding entrepreneurs to prioritize performance-driven strategies to achieve stronger competitiveness.